Homogeneidad macroeconómica dentro del Mercosur: una visión general - Arnaudo, Aldo A.; Jacobo, Alejandro D. (El Colegio de México, A.C., 1997)
Similar business fluctuations are considered a necessary condition for the harmonization of economic policies and institutions within countries involved in an economic integration process. This paper deals with the macroeconomic performance of Mercosur countries during the last twenty five years. Its aim is threefold. First, to determine whether the economic fluctuations of Mercosur countries had a similar behavior according to their duration, intensity and timing. Second, to evaluate the reaction of the economies to demand and supply shocks; an exercise which is made only for Argentina and Brazil. Third, to study simultaneously the economic fluctuations of the four countries.